MENGENAL SAHIH AL-BUKHARI - Juli Julaiha (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
Sahih al-Bukhari is the most important standard book of Hadith, and occupies a place of honor after the Qur'an. The full title of Sahih al-Bukhari is al-Jami' al-Musnad as-Sahih al-Mukhtaar min 'Umr Raslillah wa Sunanih wa Ayyamih written by Ab 'Abdullah Muhammad ibn Ismailibn Ibrahim ibn al-Mugirah ibn Bardizbah al-Ju 'fi al-Bukhari, contains about 4,000 Hadith, all of which are authentic. The contents of Sahih al-Bukhari are divided into more than 100 sections and 3,450 chapters. It starts with a discussion of revelation and ends with a discussion of monotheism. In compiling his book, Imam al-Bukhari used the arrangement and topics commonly used in the science of fiqh. The hadiths are sorted and grouped based on the fields that explain the existing parts, by mentioning in full their sanad.